THE ROLE OF VARIATIVE APPROACHES IN DEVELOPING STUDENTS' INDEPENDENCE IN LEARNING ACTIVITIES (The Conference Hub, 2025)
This article analyzes the role of variational approaches in developing students' independence in their learning activities. Variational approaches provide students with a variety of teaching methods, allowing them to independently master their own knowledge. Such approaches increase students' creative thinking, problem-solving skills, and make the learning process more effective. The article reveals the importance of variational approaches in developing students' independent learning activities.